Structural insights into the competitive inhibition of the ATP-gated P2X receptor channel - Go Kasuya (Nature Portfolio, 2017)
P2X receptors are nonselective cation channels that are gated by extracellular ATP. Here the authors present the crystal structure of chicken P2X7 with its bound competitive antagonist TNP-ATP and give mechanistic insights into TNP-ATP dependent inhibition through further computational analysis and electrophysiology measurements.